Environmental allergies and respiratory morbidities in cystic fibrosis1. Issue 9 (9th November 2012) - Collaco, Joseph M.; Morrow, Christopher B.; Green, Deanna M.; Cutting, Garry R.; Mogayzel, Peter J.
Abstract Background Cystic fibrosis (CF) is characterized by recurrent respiratory infections and progressive lung disease. Although environmental factors account for 50% of the variation in CF lung function, few specific exposures have been identified. Studies using small study samples focusing on environmental allergies in CF have had inconsistent results. Our objective was to examine the role of environmental allergies in upper and lower respiratory tract morbidities in CF. Methods A total of 1, 321 subjects with CF were recruited through the U.S. CF Twin–Sibling Study. Questionnaires were used to determine the presence/absence of environmental allergies. Questionnaires, chart review, and U.S. CF Foundation Patient Registry data were used to track outcomes. Results Within the study sample 14% reported environmental allergies. Environmental allergies were associated with a higher risk of sinus disease (adjusted OR: 2.68; P < 0.001) and nasal polyps (adjusted OR: 1.74; P = 0.003). Environmental allergies were also associated with a more rapid decline in lung function (additional −1.1%/year; P = 0.001). However, allergies were associated with a later median age of acquisition of Pseudomonas aeruginosa (6.6 years vs. 4.4 years; log rank P = 0.027). The reported use of common allergy medications, anti‐histamines and leukotriene inhibitors, did not alter the frequency of respiratory morbidities. Conclusions Environmental allergies are associated with an increased risk of sinus disease and nasal polyps and a more rapid decline in CF lung function, but may have a protective effect against the acquisition of P. aeruginosa. Prospective studies are needed to confirm these associations which have implications for more aggressive management of allergies. Pediatr Pulmonol. 2013; 48:857–864. © 2012 Wiley Periodicals, Inc.